Math, asked by nra816240, 3 months ago

If m and n are the zeroes of the polynomial x² + 7x + 7, then form a quadratic polynomial whose zeroes are 2m and 2n.​

Answers

Answered by user0888
42

Answer.

Given:-

Let f(x)=x^{2}+7x+7.

Roots of f(x) are m and n.

Let the new zeros be m' and n', where

  • m'=2m
  • n'=2n

The solution:-

By definition of zeros, f(m)=0 and f(n)=0 is true.

If m and n are zeros of the polynomial, m' and n' will be the roots of f\left(\dfrac{x}{2}  \right ), because we know that f\left( \dfrac{m'}{2} \right) =0 and f\left( \dfrac{n'}{2} \right) =0.

By above, f\left(\dfrac{x}{2} \right)=k(\dfrac{1}{4} x^{2}+\dfrac{7}{2} x+7) has two zeros m' and n'.

We choose k=4 then the polynomial is \boxed{x^{2}+14x+28}.

Solve more questions.

Question example:-

Find the sum of multiplicative inverses of the zeros of x^{2}+7x+7.

What we need to know:-

A polynomial with its coefficients reversed has the inverses of the zeros. Here we are going to prove it.

The solution:-

Let α and β be the zeros of the equation. Then α' and β' will be new zeros.

Let's solve for \alpha and \beta in terms of \alpha ' and \beta '.

  • \alpha =\dfrac{1}{\alpha '}
  • \beta =\dfrac{1}{\beta '}

This means

  • f(\alpha )=0\implies f\left( \dfrac{1}{\alpha '} \right) =0
  • f(\beta )=0\implies f\left( \dfrac{1}{\beta '} \right) =0

So, f\left( \dfrac{1}{x} \right) has \alpha ' and \beta ' as zeros.

\implies f\left(\dfrac{1}{x}  \right) =7\left( \dfrac{1}{x} \right) ^{2}+7\left( \dfrac{1}{x} \right)+1

\implies f\left(\dfrac{1}{x}  \right) = \dfrac{7}{x^{2}} ^{2}+\dfrac{7}{x} +1

Multiplying x^{2} on both sides,

x^{2}\cdot f\left(\dfrac{1}{x}  \right) =7+7x+x^{2}

We get x^{2}+7x+7 as a polynomial whose zeros are the inverses.

The sum of the inverses of the zero is hence -\dfrac{7}{7} =\boxed{-1}.

Answered by Itzheartcracer
33

Given :-

If m and n are the zeroes of the polynomial x² + 7x + 7

To Find :-

Quadratic polynomial

Solution :-

Here

α + β = m + n

m + n = -b/a

Where

b = 7

a = 1

m + n = -(7)/1

m + n = -7

Product of zeroes = αβ = mn

mn = c/a

c = 7

a = 1

mn = 7/1

mn = 7

Now

New sum of the zeroes = 2m + 2n = 2(m + n) = 2(-7) = -14

New product of zeroes = 2m × 2n = 4(m × n) = 4(7) = 28

Now

We know that

Polynomial = x² - (α + β)x + αβ

Polynomial = x² - (-14)x + 28

Polynomial = x² + 14x + 28

[tex][/tex]

Similar questions